3D Printed Ionogels In Sensors. Issue 5 (24th March 2023) - Clement, Navya; Kandasubramanian, Balasubramanian
ABSTRACT: Ionogels are a promising family of soft, conducting materials having, high ionic conductivity and wide operating temperature. 3D printing is an enabling technology undergoing, phenomenal expansion in recent years, propelling ionogels as next-generation material. This work showcases preface to ionogels, its classification, preparation, 3D printing techniques to print ionogels and properties of sensors formed from ionogels, which are imparted via various 3D printing are compared by taking into account of difference in poly ionic liquid (PIL), which is a class of polyelectrolytes, having conducting ions which are poorly coordinated, polymeric backbones with ionic liquid in every repeating unit. GRAPHICAL ABSTRACT: uf0001